2018
DOI: 10.1002/ajmg.b.32618
|View full text |Cite
|
Sign up to set email alerts
|

The molecular epidemiology of Huntington disease is related to intermediate allele frequency and haplotype in the general population

Abstract: Huntington disease (HD) is the most common monogenic neurodegenerative disorder in populations of European ancestry, but occurs at lower prevalence in populations of East Asian or black African descent. New mutations for HD result from CAG repeat expansions of intermediate alleles (IAs), usually of paternal origin. The differing prevalence of HD may be related to the rate of new mutations in a population, but no comparative estimates of IA frequency or the HD new mutation rate are available. In this study, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 50 publications
3
41
1
1
Order By: Relevance
“…In contrast, previously published research 15 has shown that the A1 haplotype is associated with elongated CAG repeat lengths. 20 Finally, we identified another variant in this region that results in a longer interrupting sequence, through the insertion of a duplicate CAA-CAG motif [i.e., 18 bp; (CAA-CAG)2-CCG-CCA, Supplementary Figure S2]. In the two pedigrees where this variant was present, carriers (n=6 HD subjects) presented 4.8 years later AOO than expected in comparison to reference interrupting sequence HD subjects (AOO percentile 60th-85 th , AOO ratio P=0.04).…”
Section: The Htt Cag-ccg Loi Variant Resulting In An Uninterrupted Cmentioning
confidence: 99%
“…In contrast, previously published research 15 has shown that the A1 haplotype is associated with elongated CAG repeat lengths. 20 Finally, we identified another variant in this region that results in a longer interrupting sequence, through the insertion of a duplicate CAA-CAG motif [i.e., 18 bp; (CAA-CAG)2-CCG-CCA, Supplementary Figure S2]. In the two pedigrees where this variant was present, carriers (n=6 HD subjects) presented 4.8 years later AOO than expected in comparison to reference interrupting sequence HD subjects (AOO percentile 60th-85 th , AOO ratio P=0.04).…”
Section: The Htt Cag-ccg Loi Variant Resulting In An Uninterrupted Cmentioning
confidence: 99%
“…It is important to note that few studies have reported the frequency of IAs and the prevalence of HD in large cohorts of admixed populations worldwide (Agostinho et al, ; Apolinário, Paiva, & Agostinho, ; Kay et al, ; RASKIN et al, ). A study by Kay et al () investigated the epidemiology of HD and IAs in 15 populations with different ethnic origins but did not analyze the situation in Brazil in relation to intermediate HD alleles, which was the aim of our investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Some groups have recently found a high prevalence of CAG repeats in the intermediate and reduced penetrance range in the background population 18 . There is also indication that the prevalence of HD, and frequency of new mutations, is correlated to the mean repeat number and prevalence of IAs in the general population.…”
mentioning
confidence: 99%